2019
DOI: 10.1002/adma.201806314
|View full text |Cite
|
Sign up to set email alerts
|

Crafting Mussel‐Inspired Metal Nanoparticle‐Decorated Ultrathin Graphitic Carbon Nitride for the Degradation of Chemical Pollutants and Production of Chemical Resources

Abstract: The development of efficient photocatalysts for the degradation of organic pollutants and production of hydrogen peroxide (H2O2) is an attractive two‐in‐one strategy to address environmental remediation concerns and chemical resource demands. Graphitic carbon nitride (g‐C3N4) possesses unique electronic and optical properties. However, bulk g‐C3N4 suffers from inefficient sunlight absorption and low carrier mobility. Once exfoliated, ultrathin nanosheets of g‐C3N4 attain much intriguing photocatalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(175 citation statements)
references
References 60 publications
3
170
0
2
Order By: Relevance
“…They ield of H 2 O 2 with the fabricated Au/g-C 3 N 4 photocatalyst reached 1320 mmol L À1 after irradiation with light for 240 min;t his yield is 2.3-times higher than that of the pristine g-C 3 N 4 .Inthe other study,Zuo et al [60b] observed asimilar improvement in the production of H 2 O 2 production with aA u/C 3 N 4 photocatalyst. Theauthors also compared in this study the effect of different co-catalysts (Au, Ag, Pd, and Pt) on g-C 3 N 4 for the production of H 2 O 2 .T he results showed that g-C 3 N 4 loaded with Au NPs exhibited the best performance for the production of H 2 O 2 .T he enhanced H 2 O 2 production was attributed to the efficient separation of charge carriers between the finely dispersed Au NPs and g-C 3 N 4 .M ore recently,C ai et al [61] fabricated silver-decorated ultrathin g-C 3 N 4 nanosheets (Ag@U-g-C 3 N 4 -NS;F igure 10 a,b). The Ag@U-g-C 3 N 4 -NS exhibited am uch stronger absorption of light in the 200-2000 nm range (Figure 10 c), as aresult of the localized surface plasmon resonance (SPR) of the loaded Ag NPs.I na ddition, the Ag NPs also effectively separated the photogenerated carriers by forming aSchottky barrier, while the large specific surface area of the ultrathin nanosheet construction could facilitate the transfer of electrons to participate in photocatalytic reactions,t hereby leading to the improved photocatalytic performance (Figure 10 d).…”
Section: Loading Of Noble Metal Nanoparticlesmentioning
confidence: 95%
“…They ield of H 2 O 2 with the fabricated Au/g-C 3 N 4 photocatalyst reached 1320 mmol L À1 after irradiation with light for 240 min;t his yield is 2.3-times higher than that of the pristine g-C 3 N 4 .Inthe other study,Zuo et al [60b] observed asimilar improvement in the production of H 2 O 2 production with aA u/C 3 N 4 photocatalyst. Theauthors also compared in this study the effect of different co-catalysts (Au, Ag, Pd, and Pt) on g-C 3 N 4 for the production of H 2 O 2 .T he results showed that g-C 3 N 4 loaded with Au NPs exhibited the best performance for the production of H 2 O 2 .T he enhanced H 2 O 2 production was attributed to the efficient separation of charge carriers between the finely dispersed Au NPs and g-C 3 N 4 .M ore recently,C ai et al [61] fabricated silver-decorated ultrathin g-C 3 N 4 nanosheets (Ag@U-g-C 3 N 4 -NS;F igure 10 a,b). The Ag@U-g-C 3 N 4 -NS exhibited am uch stronger absorption of light in the 200-2000 nm range (Figure 10 c), as aresult of the localized surface plasmon resonance (SPR) of the loaded Ag NPs.I na ddition, the Ag NPs also effectively separated the photogenerated carriers by forming aSchottky barrier, while the large specific surface area of the ultrathin nanosheet construction could facilitate the transfer of electrons to participate in photocatalytic reactions,t hereby leading to the improved photocatalytic performance (Figure 10 d).…”
Section: Loading Of Noble Metal Nanoparticlesmentioning
confidence: 95%
“…Highly redox active materials are an important tool for the degradation of refractory organic water and soil contaminants. [ 1–7 ] Nanoscale zero valent (NZVI) has been used for in situ groundwater remediation for more than two decades. [ 8–12 ] NZVI is a strong reductant that readily dechlorinates chlorinated solvents and antibiotics, and reduces and immobilizes heavy metals and radionuclides.…”
Section: Figurementioning
confidence: 99%
“…Carbon nitrides (CNs) are exclusive class of materials that have gained significant importance in various areas of energy storage and conversion (batteries, supercapacitors, and fuel cells), energy production (photoreduction of CO 2 , photocatalytic water splitting), catalysis, optoelectronics, gas capture, environmental remediation, and sensing in the past few years. These application perspectives could be attributed to their outstanding physico‐chemical properties such as basicity, low density, good chemical/thermal stability, and tunable electronic parameters .…”
Section: Introductionmentioning
confidence: 99%